Implicit Function Theorems for Nondifferentiable Mappings - Bian, W. (Journal of optimization theory and applications, 2006)
Sufficient conditions are given for a mapping to be y-G inverse differentiable. Constrained implicit function theorems for y-G inverse differentiable mappings are obtained, where the constraint is taken to be either a closed convex cone or a closed subset. A theorem without assuming the y-G inverse differentiability in a finite-dimensional space is also presented. [PUBLICATION ABSTRACT]